2000
DOI: 10.1159/000031158
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Plateletpheresis Induces the Interaction of Activated Platelets with White Blood Cells

Abstract: Background and Objectives: In this study we investigated whether platelet activation during apheresis results in the binding of platelets to white blood cells. Material and Methods: Analysis of platelet–leukocyte interaction was performed using multiparameter, three–color flow cytometry. Results: Over the duration of the procedure, there was an increase in the surface expression of CD62p (P–selectin) and CD63 (p<0.05), and also in the binding of platelets to monocytes (p<0.05), neutrophilic granulocytes (p<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Differences in the degree of binding in dependency of the WBC subclasses have already been described by other authors. Stuard et al 25 and Gawaz et al 26 detected this form of interaction during hemodialysis, Rinder et al 27 during cardiopulmonary bypass, and our group during plateletpheresis 28 . In 1989, Larsen et al 29 showed with in vitro tests that P‐selectin mediates the binding to neutrophil granulocytes and monocytes.…”
Section: Discussionmentioning
confidence: 75%
“…Differences in the degree of binding in dependency of the WBC subclasses have already been described by other authors. Stuard et al 25 and Gawaz et al 26 detected this form of interaction during hemodialysis, Rinder et al 27 during cardiopulmonary bypass, and our group during plateletpheresis 28 . In 1989, Larsen et al 29 showed with in vitro tests that P‐selectin mediates the binding to neutrophil granulocytes and monocytes.…”
Section: Discussionmentioning
confidence: 75%
“…This finding is supported by Gutensohn et al . [33], who reported that the Amicus process is highly traumatic and causes activation of platelets and their interaction with monocytes and granulocytes [33]. Another study showed that platelets from Amicus have increased fibrinogen receptor activation, increased size of platelet aggregates, increased formation of microparticles, increased degranulation, decreased von Willebrand factor receptor surface expression and also decreased responses to in vitro agonist stimulation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Such responses may be exacerbated further by activated platelets which, upon transfusion, may not only induce WBC activation and/or secretion of proinflammatory cytokines and strengthen local and systemic inflammatory reactions, but also provide an additional stimulus to the coagulation system. From the quality perspective, minimal activation of PCs is desirable for preserving platelet function, reducing levels of platelet‐derived cytokines and for in vivo efficacy of the product intended for transfusion [33,46]. Only a comparison of data obtained from large clinical trials in well‐defined cohort(s) of patients would provide realistic information on the risk and/or clinical benefit of the filtered BC‐PCs or apheresis products (some of which contain a high proportion of activated platelets) in terms of relative dose of platelets and/or transfusion reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte activation could also be caused by serum components such as activated complement, thrombin or the interaction of activated platelets and WBC. P‐selectin on activated platelets mediates the adhesion of platelets, especially to monocytes and neutrophils [17–19].…”
Section: Discussionmentioning
confidence: 99%